The Effect Of Mother-Baby Massage On Bounding Attachment - Anis Nikmatul Nikmah; Galuh Pradian Yanuaringsih (Universitas Aisyiyah Yogyakarta, 2020)
Baby massage is a touch therapy in infants. It is the simplest and easiest way of communication, which makes contact between mother and her baby. The touch and the view of parental affection on her baby will drain the strength of love between the two. The results showed that the baby massage applied in a structured parenting program could decrease the incidence of post partum blues, the symptoms of mother depression, increasing the interaction between mothers and infants. The research method uses quasyexperimental with non rondom design pretests and posttest with control group design. The population is a pospartum mother and a healthy baby at the age of 2 weeks-1 month. Sampling techniques use acidental sampling with a large sample of 32 respondents divided into treatment and control groups. The process of data collection is done by giving a pre ters bounding atachment then given the next massage treatment done postest bounding atachment. Data analysis is used in pairs and no paired sample of the normality test. Based on the results of the analysis, there is an effect of a mother-baby massage on bounding attachment in the treatment group, and there is a difference in the result of bounding score attachment between the treatment group and the control group. Parental touches are the fundamental for the development of communication that will lead to reciprocal love. The baby massage will give more benefits to the mother and baby.